FUNCTIONAL SKILLS TRAINING WITH ABA PROMOTING THE AUTONOMY OF STUDENTS WITH INTELLECTUAL DISABILITIES IN INCLUSIVE SCHOOL CONTEXTS (Editora Impacto Científico, 2025)
This research discusses the impact of Applied Behavior Analysis (ABA) on promoting autonomy and participation of students with intellectual disabilities in inclusive school settings. The aim is to understand how ABA-based behavioral strategies can foster the development of functional and social skills within the educational environment. The study is justified by the growing demand for evidence-based pedagogical practices that ensure inclusion and meaningful learning for these students. A qualitative methodology with bibliographic and exploratory-descriptive design was used, analyzing academic literature from 2000 to 2024. The study developed through critical reading and thematic categorization of data regarding the effects of ABA in schools, especially in teaching daily living skills, communication, and adaptive behavior. Results show that systematic use of reinforcers, clear instructions, structured teaching, and curricular adaptations significantly contribute to greater independence, engagement, and participation in school activities. Discussions highlight the importance of the Specialized Educational Support (AEE) and teacher training in the ethical and effective application of behavioral strategies. It is concluded that ABA is a powerful and promising tool for strengthening school inclusion when tailored to students' needs and integrated into pedagogical planning.